ANALYSIS OF DIGITAL PROMOTION AND SCHOOL IMAGE ON STUDENTS' DECISIONS TO CHOOSE A SCHOOL THROUGH INTEREST AS A MEDIATION VARIABLE AT STATE VOCATIONAL SCHOOL 2 PEMATANG SIANTAR - Jerriwanto Pontus Regen Sitorus; Husni Muharram Ritonga; Nurafrina Siregar (RADJA PUBLIKA, 2026)
The development of information technology in the past five years has significantly impacted the way schools communicate and attract prospective students, with social media, websites, and digital platforms becoming the primary sources of information for parents and students. This study aims to analyze the influence of digital promotion and school image on school choice decisions through interest as a mediating variable at SMK Negeri 2 Pematang Siantar. Digital promotion, which involves a series of marketing activities utilizing digital media, can build closer relationships with audiences and influence school choice decisions. School image, formed through the experiences, information, and achievements displayed, plays a significant role in shaping prospective students' perceptions of the quality of education offered. This study used a quantitative method with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis to test the direct and indirect effects between the variables studied. The results showed that digital promotion had a positive and significant effect on student choice decisions and interest. School image also had a positive effect on interest, although it was not significant on the decision to choose directly. Student interest proved to be a significant mediating variable between digital promotion, school image, and choice decisions. These findings provide important contributions to school communication strategies, particularly in enhancing digital promotion and strengthening the school's image to attract new prospective students.